A De Novo Transcriptome Analysis Identifies Cold-Responsive Genes in the Seeds of Taxillus chinensis (DC.) Danser. (6th July 2022) - Fu, Jine; Wan, Lingyun; Song, Lisha; He, Lili; Jiang, Ni; Long, Hairong; Huo, Juan; Ji, Xiaowen; Hu, Fengyun; Wei, Shugen; Pan, Limei
Abstract : Taxillus chinensis (DC.) Danser, a parasitic plant of the Loranthaceae family, grows by attacking other plants. It has a long history of being used in Chinese medicine to treat multiple chronic diseases. We previously observed that T. chinensis seeds are sensitive to cold. In this study, we performed transcriptome sequencing for T. chinensis seeds treated by cold (0°C) for 0 h, 12 h, 24 h, and 36 h. TRINITY assembled 257, 870 transcripts from 223, 512 genes. The GC content and N50 were calculated as 42.29% and 1, 368, respectively. Then, we identified 42, 183 CDSs and 35, 268 likely proteins in the assembled transcriptome, which contained 1, 622 signal peptides and 6, 795 transmembrane domains. Next, we identified 17, 217 genes (FPKM > 5 ) and 2, 333 differentially expressed genes (DEGs) in T. chinensis seeds under cold stress. The MAPK pathway, as an early cold response, was significantly enriched by the DEGs in the T. chinensis seeds after 24 h of cold treatment. Known cold-responsive genes encoding abscisic acid-associated, aquaporin, C-repeat binding factor (CBF), cold-regulated protein, heat shock protein, protein kinase, ribosomal protein, transcription factor (TF), zinc finger protein, and ubiquitin were deregulated in the T. chinensis seeds under cold stress. Notably, the upregulation of CBF gene might be the consequences of the downregulation of MYB and GATA TFs. Additionally, we identified that genes encoding CDC20, YLS9, EXORDIUM, and AUX1 and wound-responsive family protein might be related to novel mechanisms of T. chinensis seeds exposed to cold. This study is first to report the differential transcriptional induction in T. chinensis seeds under cold stress. It will improve our understanding of parasitic plants in response to cold and provide a valuable resource for future studies.